2007
DOI: 10.1115/1.2813131
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Modeling and Geometrical Influence on the Hydraulic Performance of a Control Valve

Abstract: The ability to understand and manage the performance of hydraulic control valves is important in many automatic and manual industrial processes. The use of computational fluid dynamics (CFD) aids in the design of such valves by inexpensively providing insight into flow patterns, potential noise sources, and cavitation. Applications of CFD to study the performance of complex three-dimensional (3D) valves, such as poppet, spool, and butterfly valves, are becoming more common. Still, validation and accuracy remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…Also, as the valve opening increases, energy dissipation increases. This phenomenon was also found by Palau-Salvador et al (2008) in a control valve. The flow field contained several vortexes and a wall jet that hit the piston with high velocity.…”
Section: Effects Of Throttling Structures On Velocity and Structure Isupporting
confidence: 74%
“…Also, as the valve opening increases, energy dissipation increases. This phenomenon was also found by Palau-Salvador et al (2008) in a control valve. The flow field contained several vortexes and a wall jet that hit the piston with high velocity.…”
Section: Effects Of Throttling Structures On Velocity and Structure Isupporting
confidence: 74%
“…In the grid independency test of various meshes, Chern et al (2013) also chose the pressure difference as the judgment parameter, ranging from 17.3 kPa to 21.3 kPa under similar conditions. Moreover, in a control valve (Palau-Salvador et al, 2008), with similar inlet velocities, they found that the pressure different inside changes from 0.2 MPa to 1.4 MPa. Though these published experimental or numerical data cannot validate our model directly, this comparison suggests reliability of our results and the correctness of the simulation.…”
Section: Comparison With Similar Simulationsmentioning
confidence: 99%
“…Fu et al (2007) analyzed the characteristics of flow through a throttling valve with different pressures. Palau-Salvador et al (2008) carried out a 3D modeling of a control valve, and its geometrical influence on hydraulic Journal of Zhejiang University-SCIENCE A (Applied Physics & Engineering) ISSN 1673-565X (Print); ISSN 1862-1775 (Online) www.zju.edu.cn/jzus; www.springerlink.com E-mail: jzus@zju.edu.cn performance was observed. Chattopadhyay et al (2012) investigated the flow through a spool type pressure regulating valve to analyze the flow structure inside it.…”
Section: Introductionmentioning
confidence: 99%
“…The above differential partial equations are implemented in the computational module of the Ansys CFX program [7,8,10]. To effectively solve the system of equations describing the turbulent flow of the fluid, it is necessary to use boundary conditions that guarantee the uniqueness of the solution and affect the computational process in the area analyzed.…”
Section: Fluid Flow Mathematical Modelmentioning
confidence: 99%